2019
DOI: 10.1016/j.ebiom.2019.05.027
|View full text |Cite|
|
Sign up to set email alerts
|

poFUT1 promotes endometrial decidualization by enhancing the O-fucosylation of Notch1

Abstract: Background Endometrial stromal cell decidualization is critical for embryo implantation. Dysfunctional decidualization leads to implantation failure, miscarriage and even pregnancy associated disorders in subsequent pregnancy trimesters. Protein glycosylation is involved in many physiological and pathological processes. Protein O-fucosyltransferase 1 (poFUT1) is the key enzyme for the O-fucosylation of proteins. However, the role and mechanism of poFUT1 in human endometrial stromal cell decidualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…CoV-2 protein orf8 might support O-glycosylation by binding POGLUT2, POGLUT3, two O-glucosyltransferases, and POFUT1, an O-fucosyltransferase (Table 1). These enzymes have been shown to be pivotal for the proper glycosylation and presentation on the plasma membrane of the NOTCH1 receptor (Takeuchi et al, 2018;Yang et al, 2019;Okamura and Saga, 2008), confirming once more the importance of glycan processing in the maturation and transport of CoV-2 S and other proteins.…”
Section: Introductionmentioning
confidence: 78%
“…CoV-2 protein orf8 might support O-glycosylation by binding POGLUT2, POGLUT3, two O-glucosyltransferases, and POFUT1, an O-fucosyltransferase (Table 1). These enzymes have been shown to be pivotal for the proper glycosylation and presentation on the plasma membrane of the NOTCH1 receptor (Takeuchi et al, 2018;Yang et al, 2019;Okamura and Saga, 2008), confirming once more the importance of glycan processing in the maturation and transport of CoV-2 S and other proteins.…”
Section: Introductionmentioning
confidence: 78%
“…Decidualization is the differentiation of elongated, fibroblast-like mesenchymal cells into rounded, epithelioid-like cells under stimulation by progestogen and cyclic adenosine monophosphate (c-AMP) [6,7]. The morphological differentiation and hypermetabolic state of human endometrial stromal cells (HESCs) make them ready for subsequent embryo implantation [8], [9], [10]. However, few studies have investigated the molecular mechanisms underlying impaired decidualization during RIF.…”
Section: Introductionmentioning
confidence: 99%
“…The poFuT1 expression was revealed to increase during the proliferation phase of the menstrual cycle; however, poFuT1 expression was reported to decrease in the endometrium during miscarriage. These results indicated that poFuT1 serves a key role in endometrial decidualisation, and may be therapeutically targeted to prevent spontaneous abortion (72).…”
Section: Applications Of a Mouse Model Of Menstruationmentioning
confidence: 82%